1989
DOI: 10.1111/j.1365-2826.1989.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex, Intrauterine Position and Androgen Manipulation on the Development of Brain Aromatase Activity in Fetal Ferrets

Abstract: Experiments were conducted to explore the possible relationship between testicular androgen secretion and the development of brain aromatase activity in fetal ferrets. Aromatase activity in the preoptic+ mediobasal hypothalamus and temporal lobe was s!milar in fetuses of both sexes between embryonic Days 26 and 36 even though whole body androgen content was invariably higher in males than females. Whole body androgen content was significantly higher in females located caudally (downstream) from two or more as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 36 publications
3
30
1
Order By: Relevance
“…An obvious possibility is that in males exposure to testicular androgen over a prolonged prenatal and/or immediate postparturient period sensitizes the developing brain to respond to the relatively slight increments in circulating testosterone that occur neonatally in this species, as in other species including the rat (14). The results of a recent study (39) support such a conclusion.…”
Section: Developmental Effects Of Oestrogen and Androgensupporting
confidence: 79%
See 3 more Smart Citations
“…An obvious possibility is that in males exposure to testicular androgen over a prolonged prenatal and/or immediate postparturient period sensitizes the developing brain to respond to the relatively slight increments in circulating testosterone that occur neonatally in this species, as in other species including the rat (14). The results of a recent study (39) support such a conclusion.…”
Section: Developmental Effects Of Oestrogen and Androgensupporting
confidence: 79%
“…Evidence presented earlier in this review showed that the availability of androgenic substrate to the neural aromatizing enzymes is consistently greater in male than in female ferrets throughout the last quarter of gestation, when the steroids act to organize the Mn-POA/AH. Experimental manipulations of androgen receptor activation (either blockade via transplacental administration of the anti-androgen, flutamide, or activation via transplacental DHT) failed to influence the level of aromatase activity in POA + hypothalamus or temporal lobes of foetal ferrets (14). This finding implies that the increased level of oestrogen biosynthesis which apparently occurs in the male ferret's POA/AH must result from increased availability of androgenic substrate in foetuses of this sex, as opposed to an androgendependent activation of the aromatase enzyme such as occurs in the adult mammalian nervous system (102).…”
Section: Tonic Pulsatile Lh Secretionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are sex differences in exposures to androgens and estrogens that appear to underlie normal reproductive neuroendocrine development [85,164,146]. Aberrations in these developmental patterns in females can cause masculinization (acquisition of a male-typical trait) or defeminization (loss of a female-typical trait), and in males, may cause feminization or demasculinization (comparably defined).…”
Section: Introduction To Development Of Reproductive Neuroendocrine Cmentioning
confidence: 99%